2022
DOI: 10.1002/cctc.202200762
|View full text |Cite
|
Sign up to set email alerts
|

CeO2 Nanorod@NiPhy Core‐shell Catalyst for Methane Dry Reforming: Effect of Simultaneous Sintering Prevention of CeO2 Support and Active Ni

Abstract: Preventing the sintering of nano-catalyst is crucial to maintain their performance especially for high-temperature reactions such as CO 2 reforming of methane (DRM) reaction. In this paper, we design CeO 2 nanorod@Ni phyllosilicate (CeO 2 @NiPhy) catalysts with different NiPhy shell thickness to simultaneously preserve the morphology of CeO 2 nanorod and prevent the sintering of Ni. Compared with Ni/CeO 2 supported catalyst, CeO 2 @NiPhy core-shell catalyst with a shell thickness of 9 nm exhibits much better p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…[ 149 ] Nevertheless, non‐noble metal catalysts tend to deactivate quickly due to the rapid coke formation and nanoparticle sintering. [ 140,150 ]…”
Section: Single‐atom Catalysts For Thermocatalytic Co2 Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 149 ] Nevertheless, non‐noble metal catalysts tend to deactivate quickly due to the rapid coke formation and nanoparticle sintering. [ 140,150 ]…”
Section: Single‐atom Catalysts For Thermocatalytic Co2 Conversionmentioning
confidence: 99%
“…[149] Nevertheless, non-noble metal catalysts tend to deactivate quickly due to the rapid coke formation and nanoparticle sintering. [140,150] Reducing the size of metal particles can significantly enhance the activity while inhibiting the undesirable coking of metal catalysts, so SACs with isolated metal atom as active sites are increasingly used in DRM reactions, as shown in Table 1. Akri et al found that Ni single atoms supported by hydroxyapatite (0.5Ni 1 /HAP) possessed a much more superior coke resistance ability with negligible coke deposition, compared to 10Ni/HAP (Insets: Raman spectra of spent 0.5Ni 1 /HAP and 10Ni/HAP catalysts and STEM image of spent 0.5Ni 1 /HAP catalyst after reaction at 750 °C for 7 h).…”
Section: Co 2 Reforming Of Methane (Drm)mentioning
confidence: 99%
“…To address the deactivation issues in the DRM process, tremendous efforts have been dedicated to the modification of catalysts. For example, the doping of W and Si facilitated the Ni aluminate formation in Ni/Al 2 O 3 catalysts, in which Ni was highly dispersed and anchored onto the support due to the strong interaction, thus preventing coke formation . Besides the strong metal–support interactions, Ni nanoparticles with an average size of 4.3 nm were confined within the porous carbon derived from pinewood sawdust, inhibiting the metal agglomeration (4.6 nm after 500 min DRM reaction at 700 °C) .…”
Section: Introductionmentioning
confidence: 99%